Ritual and Popular Religion in Catholic Germany at the Time of the Reformation - Scribner, R. W. (The journal of ecclesiastical history, 1984)
‘Popular religion’ has of late been a much-discussed subject among historians of early modern Europe. Most of the best work has been on France, by French and North American scholars, while for Germany the subject is virtually ignored. Oddly enough, serious scholarship on ‘popular’ or ‘folk’ religion began in Germany at the opening of this century, and by the 1920s a major new field of historical enquiry had been established under the banner of religiöse Volkskunde. However, historians left the study of German popular religion to folklorists, a tendency perhaps reinforced by the rather dubious reputation the discipline of Volkskunde acquired under the Nazi regime. Both before and after 1945, folklore scholars have contributed numerous important studies of popular religion in early modern Germany, but historians have been reluctant to follow in their footsteps. Some of this reluctance may be explained by the absence of precise definition as to what is meant by ‘popular religion’. It is often defined through the use of polar opposites, in terms such as ‘official’ and ‘popular’ religion. The former is institutional religion, the latter that which deviates from institutional norms. Another definition invokes an opposition between theory and practice.